Knowledge and Practice Regarding Breastfeeding among Physician Mothers in Tertiary Care Centre - Mathema, Smriti; Adhikari, Pritha; Bhattarai, Puja (Journal of Nepalgunj Medical College, 2025)
Introduction: During medical school and residency training, physicians are taught that breastfeeding is the preferred feeding for all infants. Evidence is accumulating that while physician mothers have a high rate of breastfeeding initiation, they face significant obstacles to sustained breastfeeding. Aims: This study aimed to assess personal breastfeeding intentions and behavior of a diverse group of physician mothers from various medical specialties. Methods: This study was a questionnaire-based descriptive cross-sectional study conducted among physician mothers in a tertiary care center located in Kathmandu, Nepal between October 2024 to April 2025. The questionnaire contained 35 items about maternal demographics, breastfeeding practices, environmental factors, and breastfeeding advocacy. Descriptive statistics, frequency tables, and percentages were calculated using SPSS. Results: Ninty-two physician mothers participated in the study. Majority of them had fairly adequate knowledge towards various correct breastfeeding practices, however only 12% were able to successfully breastfeed exclusively whereas most of the mothers chose to give a combination of formula and breastfeeding. Only 73 (79.3%) doctors reported that they felt they actively promote breastfeeding among their women patients. Conclusion: Even mothers who are medical professionals experience, and often cannot overcome, difficulties with breastfeeding. Women in medicine need enhanced breastfeeding support and services/resources. Advocacy is needed, in our work environments, for better breastfeeding support not only for our physician colleagues, but also for all lactating employees within our institutions.